2010
DOI: 10.1111/j.1478-3231.2010.02347.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α regulates the expression of genes in hypoxic hepatic stellate cells important for collagen deposition and angiogenesis

Abstract: Background/Aims Several studies have shown that regions of hypoxia develop in the liver during chronic injury. Furthermore, it has been demonstrated that hypoxia stimulates the release of mediators from hepatic stellate cells (HSCs) that may affect the progression of fibrosis. The mechanism by which hypoxia modulates gene expression in HSCs is not known. Recent studies demonstrated that the hypoxia-activated transcription factor, hypoxia-inducible factor-1α (HIF-1α), is critical for the development of fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 44 publications
6
121
1
1
Order By: Relevance
“…Our finding that HIF1 regulates cP4H subunits corresponds with previous in vitro studies in different cell types, including fibroblasts and hepatoma cells, which suggest that HIF1 regulates cP4HI and cP4HII expression (Copple et al, 2011;Grimmer et al, 2006;Hofbauer et al, 2003;Takahashi et al, 2000). This raises the possibility that HIF1-mediated regulation of cP4Hs is a broad phenomenon that is not restricted to chondrocytes.…”
Section: Research Articlesupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding that HIF1 regulates cP4H subunits corresponds with previous in vitro studies in different cell types, including fibroblasts and hepatoma cells, which suggest that HIF1 regulates cP4HI and cP4HII expression (Copple et al, 2011;Grimmer et al, 2006;Hofbauer et al, 2003;Takahashi et al, 2000). This raises the possibility that HIF1-mediated regulation of cP4Hs is a broad phenomenon that is not restricted to chondrocytes.…”
Section: Research Articlesupporting
confidence: 89%
“…While cP4HI is the main  subunit in most cell types, in chondrocytes it is cP4HII (Myllyharju, 2003;Myllyharju and Kivirikko, 2004). Previous in vitro studies have raised the possibility that HIF1 may regulate cP4Hs in chondrocytes and other cell types (Copple et al, 2011;Grimmer et al, 2006;Hofbauer et al, 2003;Takahashi et al, 2000). Therefore, the expression of cP4H subunits was first analyzed in chondrocyte primary culture.…”
Section: Hif1 Regulates Cp4h Expression In the Growth Platementioning
confidence: 99%
“…Apolipoprotein L domain containing 1 (APOLD1) is a new endothelial cell early response protein that may play a role in regulation of endothelial cell signaling and vascular function (Regard et al, 2004). APOLD1 is also found to be upregulated by hypoxia (Copple et al, 2011). Angiopoietin-like 4 (ANGPTL4) gene is induced under hypoxic (low oxygen) conditions in endothelial cells and is the target of peroxisome proliferation activators, which also act as an apoptosis survival factor for vascular endothelial cells (Kim et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…HIFs are the master regulators of oxygen homeostasis and regulate the expression of many genes involved in glycolysis, glucose transport, and synthesis of inflammatory and proangiogenic cytokines [89][90][91] . The HIF-1α protein is rapidly degraded under normoxic conditions, whereas hypoxia enhances HIF-1α levels by inhibiting its degradation [92][93][94] . HIF-1α has been implicated in many models of liver injury [95] and it has been reported that feeding mice for 4 wk with the Lieber-DeCarli diet increases HIF-1α mRNA, protein, and DNA-binding activity in the liver.…”
mentioning
confidence: 99%